Programa de educação e prevenção em saúde bucal nas escolas: análise crítica de publicações nacionais - Castro, Christian Olveira de; Oliveira, Katiane Savazzini de; Carvalho, Raquel Baroni de; Garbin, Cléa Adas Saliba [UNESP]; Bueno, Raphael Nunes (My University, 2012)
Objective: To conduct a survey on national databases about Oral Health Program (OHP) publications in schools, in the last eleven years. Material and Methods: A survey was conducted in two main bases of national publications in the field of dentistry: Bireme and Scielo. To start the research, it was used the articles theme/subject. In the search, it was used the keywords 'oral health education', 'programs and oral health and dentistry', 'programs and oral health and education'. Results: A total of 20 publications were selected. From these, seven (35%) had the aim to evaluate educational methods used in OHP, 12 (60%) evaluated the effectiveness of the OHP itself developed in the school and one (5%) reported the experience of OHP. Only two publications did not get positive results and the other eighteen obtained advantageous results. Conclusion: In the national scientific literature, there are few publications about the subject in question, suggesting that the successful experiences about OHP in schools must be published to be replicated in other parts of Brazil.

Objetivo: Realizar um levantamento, em bases de dados nacionais, de publicações sobre Programas de Saúde Bucal (PSB) nas escolas, nos últimos onze anos. Material e Métodos: Foi realizado um levantamento nas duas principais bases de publicações nacionais da área de Odontologia: Bireme e Scielo. A pesquisa teve como referência inicial o tema dos artigos. Foram utilizados, na pesquisa, os unitermos 'educação em saúde bucal'; 'programas and saúde bucal and odontologia'; 'programas and saúde bucal and educação'. Resultados: Ao todo, foram selecionadas 20 publicações, e destas, sete (35%) tinham como objetivo avaliar métodos educativos empregados em PSB, 12 (60%) avaliaram a eficácia do próprio PSB desenvolvido no âmbito escolar, e uma (5%) relatou a experiência de um PSB. Somente duas não obtiveram resultado positivo, e as 18 restantes obtiveram resultados vantajosos. Conclusão: Existem, na literatura científica nacional, poucas publicações sobre a temática em questão, sugerindo que as experiências exitosas sobre PSB precisam ser publicadas, para que sejam reproduzidas, também, em outras localidades do Brasil.
Education and prevention programs for oral health in schools: a critical analysis of national publications
Keywords: Education's programs; Oral health; Health promotion; Programas educativos; Saúde bucal; Promoção de saúde